PO007 Neuro-critical care: an 11-year experience. (1st December 2017) - Brown, Rachel; Hirsch, Nicholas P; Radcliffe, Jeremy; Kullmann, Dimitri M; Howard, Robin S
Abstract : Despite a rapid expansion, the provision of specialist neuro-critical care in the UK remains limited in a challenging environment. It is essential to develop clearer guidance concerning the role of specialist units; to define the indications for admission and transfer; and to provide evidence of added benefit over care in a general ICU. We describe 1366 patients admitted to the medical Neuro-Critical Care Unit (NCCU) at Queen Square over 11 years (2006–2016). Diagnostic groups included neuromuscular (404), vascular (171), autoimmune (170), epilepsy (105), tumour-related (76) and movement disorders. Indications for admission included the management of coma, profound weakness, bulbar, ventilatory and autonomic failure, status epilepticus and systemic complications of neurological disorders. The unit also has a specialist role in the management of autoimmune disorders and chronic respiratory failure reflected in the pattern of admission. Outcome compares with the best available data but assessment is complicated by the highly specialist case mix. It remains unclear whether NCCU should manage patients with common presentations of acute neurological disorders, or if the scarce resources should be focused on smaller numbers of tertiary referrals who pose the most complex and difficult management problems, to achieve the best outcomes for relatively small numbers of patients.